Waiting on the moon : artists, poets, drifters, grifters, and goddesses - Wolf, Peter, 1946- (Little, Brown and Company, 2025)
"From the legendary musical figure and former vocalist of the J. Geils Band, whose career spans more than six decades, a treasure trove of revealing vignettes, all told with gentle humor and heartrending poignancy. ... Told as a series of encounters with remarkable people over the course of a long and equally remarkable musical career, Waiting on the Moon provides a revealing glimpse of both iconic and lesser-known creative giants as they work--the forces that drive them to achievement, the demons they battle, the patterns of their human relationships"--Dust jacket.